THE RESULTS OF ENRICHMENT OF SAMPLES OF ORE DEPOSITS KAQLMAKIR USING TRADITIONAL AND LOCAL REAGENT “SI” (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In the Republic of Uzbekistan, at the beneficiation plants, for the enrichment of various ores, traditional reagents manufactured abroad are used. At present, it has become necessary to test local reagents and introduce them into the industry. Replacing traditional reagents with new ones - import-substituting reagents is relevant. Creating reagents made from local raw materials will replace the scarce traditional reagents and save a significant amount of currency.